2016
DOI: 10.1589/jpts.28.2322
|View full text |Cite
|
Sign up to set email alerts
|

Association between floating toe and toe grip strength in school age children: a cross-sectional study

Abstract: [Purpose] This study investigated the association between floating toe and toe grip strength. [Subjects and Methods] A total of 635 Japanese children aged 9–11 years participated in this study. Floating toe was evaluated using footprint images, while toe grip strength was measured using a toe grip dynamometer. All 1,270 feet were classified into a floating toe group and a normal toe group according to visual evaluation of the footprint images. Intergroup differences in toe grip strength were analyzed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 19 publications
(36 reference statements)
1
28
0
Order By: Relevance
“…Previous studies have shown that toe-grip force, the so-called toe-grip strength or toe flexor strength, decreases with age [3][4][5][6] and that decreased toe-grip strength is associated with problems with balance and walking ability and the occurrence of falls in the elderly [7][8][9][10][11]. Decreased toe-grip strength has also been observed in children and is particularly related to floating toes and flat feet [12,13]. Furthermore, it has been reported that the toe-grip strength of children is related to lower limb physical activities, such as running [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that toe-grip force, the so-called toe-grip strength or toe flexor strength, decreases with age [3][4][5][6] and that decreased toe-grip strength is associated with problems with balance and walking ability and the occurrence of falls in the elderly [7][8][9][10][11]. Decreased toe-grip strength has also been observed in children and is particularly related to floating toes and flat feet [12,13]. Furthermore, it has been reported that the toe-grip strength of children is related to lower limb physical activities, such as running [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…While xing the heel by a stopper, the grip bar was positioned using the rst proximal phalanx. Thereafter, the participants gripped the bar with the greatest possible force for approximately 3 seconds using their toes [29,30], and then the machine displayed the force meter. We also used a thermometer to check skin temperature of the lower extremity.…”
Section: Study Instrumentsmentioning
confidence: 99%
“…The literature about the incidence of floating toes in children and younger adults by nature are reported mostly by Japanese researchers [1][2][3] , although there are some reports from the other countries as an aftereffect of Weil osteotomy in adults 4,5) . Presently, it is not known whether floating toes, except for the after effect of surgery, are the Japanese specific, inherited or an effect of lifestyle or not 6) . It was reported the incidence of floating toes in Japanese infants in 2000 was about 10 times that of the incidence in 1980 7) and, over 70% of Japanese 3 to 6 years old infants were also reported to have at least one "floating toe" 8) .…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers had reported the dysfunctions concerning floating toes 10,11) . For example, lowered toe grip strength in floating toes children compared with normal toes children are reported 6) . Similarly, a decrease in toe grip strength is thought to be one of the factors causing floating toes in adults 13) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation